First record of hybridization in Caranx Lacepède, 1801 (Carangidae: Perciformes) in the Tropical Eastern Pacific Ocean - Angulo, Arturo; Molina, José Luis; Hampl, Federico; Hernández, Sebastián (Zootaxa, 2020)
During a recreational fishing trip on May 2017 to Isla Montuosa, Pacific coast of Panama (7.467472, -82.266556; 30 m depth), a specimen belonging to the genus Caranx was captured. The specimen showed an unusual combination of external characters, intermediate among the species known to occur in the Tropical Eastern Pacific (TEP), which caught the attention of the fishermen. A detailed analysis involving traditional morphology and molecular techniques revealed that the specimen corresponds to a hybrid of the species C. melampygus and C. sexfasciatus. This represents, to the best of our knowledge, the first confirmed record of hybridization within the genus and family in the TEP and the second record for the entire Pacific Ocean.